On the role of budgeting in the delegated provision of public goods under asymmetric information - Günter Krause (University of Würzburg, Department of Economics, 2004)
The present paper investigates the neglected topic of budgeting rules for public bureaucracies performing governmental activities within predetermined budgets under rules governing expenditure levels and composition. We analyze the optimal budgeting scheme, if the bureaucracy has superior information vis – vis the policymaker. It is tasked with supplying different types of public goods and is subject to costly audits. The optimal budgeting scheme for the bureaucracy is determined. It is shown that it crucially depends on the level of auditing costs. The same holds for the extent of discretion given to the bureaucracy about levels and composition of public expenditures.
Keywords: H61; H41; 330; Öffentliche Finanzplanung; Bürokratietheorie; Öffentliches Gut; Asymmetrische Information; Öffentliche Finanzkontrolle; Kosten; Theorie